STUDI IN SILICO METABOLIT SEKUNDER DALAM TANAMAN TAHONGAI (Kleinhovia hospita L.) SEBAGAI KANDIDAT AGEN TERAPI KARSINOMA HEPATOSELULER TERTARGET RESEPTOR c-MET (IN SILICO STUDY OF SECONDARY METABOLITES IN TAHONGAI PLANT(Kleinhovia hospita L.) AS A CANDIDATEFOR HEPATOCELLULER CARCINOMA THERAPEUTIC AGENT TARGETING c-MET RECEPTOR) - Cahyaningrum, Lydia; Rubianti, Retno; Mahira, Tsania; Gabriel, Kevin; Rusdin, Agus; Novitasari, Dhania (Indonesian Journal of Pure and Applied Chemistry, 2024)
Hepatocellular carcinoma (HCC) is the fourth leading cause of cancer-related mortality in the world, mainly caused by chronic disease or virus. Prior studies have documented that the upregulation of c-MET can trigger the cancer progression, hence c-MET has been widely explored as target therapy for HCC. Tahongai plant (Kleinhovia hospita L.) has known to possess several biological effects, including anticancer activity. However, the molecular mechanism in this plant has not been studied yet. In this study, the bioactive constituents from Tahongai were evaluated based on the physicochemical features and molecular interaction in c-MET through in silico approaches. The druglikeness of each compound was checked through SwissADME, while the pharmacokinetic profile was predicted through preADMET webtool. The pharmacophore screening and molecular docking against c-MET were assessed using LigandScout and Autodock, respectively. Out of 14 selected compounds, only one (astragalin) did not pass the Lipinski rule, and most of the compounds demonstrated good ADMET profile. Eleutherol was choosen as the hit compound based on pharmacophore studies, and stibostemin G was potential to inhibit c-MET based on similar molecular interaction compared to its native ligand through molecular docking analysis. Further confirmation is urged to prove its anticancer effect from Tahongai against HCC, particulary targeting on c-MET